Maturation of loquat fruit (Eriobotrya japonica Lindl.) under Spanish growing conditions and its postharvest performance - González L.; Lafuente M.T.; Zacarías L. (First international symposium on loquat, 2003)
Changes in fruit colour, acidity, soluble solids content, respiration rate and ethylene production were determined in loquat fruit cv. Algerie, throughout maturation and during postharvest storage at 2 degrees C. Maturation-associated changes appeared not to be coordinated, since fruit colour progressively increased; the decline in fruit acidity was initiated latter than the increase in soluble solids content. Fruit respiration and ethylene production rates decreased through maturation, also at 20 degrees C. The ripening physiology of Algerie loquat fruit can be considered as non-climacteric. Weight loss rate increased during fruit storage at 2 degrees C and was enhanced after simulation of shelf-life conditions. Colour development progressed, but soluble solids content remained with minor alterations. Fruit acidity decreased during cold storage and more markedly after fruit rewarming. Stored loquat fruits lose their characteristic flavour due to an unbalanced ratio between acids and sugars. Thus, the loss of acidity is the main factor affecting loquat fruit quality during cold storage.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)